2022
DOI: 10.1186/s40981-022-00590-9
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management with remimazolam in a patient with Child-Pugh C liver cirrhosis: a case report

Abstract: Background Remimazolam is a new ultra-short-acting benzodiazepine, and its sedative effect is prolonged in patients with hepatic impairment. This is the first report of remimazolam anesthesia in a patient with Child-Pugh C liver cirrhosis. Case presentation A 52-year-old female was diagnosed with tongue cancer and scheduled for partial glossectomy. Preoperative examinations revealed Child-Pugh C liver cirrhosis, but the pathogenesis was unknown. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Nonetheless, BIS values remained at reassuring levels during the anesthetic, and flumazenil was still required at the conclusion of surgery. Uchida et al 10 and Onoda and Suzuki 11 used remimazolam as an anesthetic for cirrhotic patients and maintained the patient’s dose at a level lower than the recommended dose based on BIS values. Further studies are necessary to determine appropriate dose ranges for different categories of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, BIS values remained at reassuring levels during the anesthetic, and flumazenil was still required at the conclusion of surgery. Uchida et al 10 and Onoda and Suzuki 11 used remimazolam as an anesthetic for cirrhotic patients and maintained the patient’s dose at a level lower than the recommended dose based on BIS values. Further studies are necessary to determine appropriate dose ranges for different categories of patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the loss of consciousness was faster after propofol versus remimazolam induction (46 versus 66 s), blood pressure was significantly lower after propofol induction. 103 Japan VATS Anaesthesia 1 100% Anaphylaxis Hong 9 Korea Arthroscopy Anaesthesia 1 0% Horikoshi 10 Japan Laparoscopy Anaesthesia 1 100% Delayed emergence Huang 11 China LMA insertion Anaesthesia NA 0% Hwang 12 Korea Teratoma resection Anaesthesia 2 0% Kawasaki 13 Japan Liver transplantation Anaesthesia 1 0% Kida 14 Japan CABG Anaesthesia 1 100% Tolerance Kim 107 Korea All kinds Anaesthesia 5 100% Anaphylactoid shock Kim 15 Korea THA Anaesthesia 1 100% Psychogenic coma Kim 16 Korea Laparotomy Anaesthesia 1 0% Kitaura 17 Japan TMVR Anaesthesia 1 0% Koh 18 Japan Spine Anaesthesia 1 100% Heart failure Lee 19 Korea RALP Anaesthesia 1 0% Liu 110 China RALP Anaesthesia 1 100% Precipitation Matsumoto 20 Japan Liver transplantation Anaesthesia 1 0% Matsuo 111 Japan Orthopaedic Anaesthesia 1 100% Precipitation Nakayama 21 Japan Minor orthopaedic Anaesthesia 2 0% Onoda 22 Japan Laparoscopy Anaesthesia 1 0% Saito 23 Japan Cardiac Anaesthesia 1 100% Hypotension Sasaki 112 Japan Dental Anaesthesia 1 100% Precipitation Sato 24 Japan Trepanation Anaesthesia 1 0% Sato 25 Japan Cardiac Anaesthesia 1 100% Hypertension Singal 102 USA Endoscopy Anaesthesia 1 100% Delayed emergence Suzuki 26 Japan ENT Anaesthesia 1 100% Delayed emergence Takemori 27 Japan RALP Anaesthesia 1 100% Delayed emergence Tsurumi 104 Japan Minor orthopaedic Anaesthesia 1 100% Anaphylaxis Uchida 28 Japan ENT Anaesthesia 1 100% Delayed emergence Uchida 29 Japan TEVAR Anaesthesia 1 100% Delayed emergence Uchida 106 Japan Skin graft; laparoscopy Anaesthesia 2 100% Anaphylaxis Yamada 30 Japan Neurosurgery Anaesthesia 3 0% Yamadori 31 Japan Laparotomy Anaesthesia 1 0% Yamamoto …”
Section: Discussionmentioning
confidence: 99%
“…Stöhr et al 125 demonstrated that after a single dose of remimazolam, severe hepatic impairment (Child–Pugh C) is associated with 38% slower elimination of remimazolam, and end-stage renal disease is associated with urine concentrations of the metabolite three times higher than normal, 4 h after bolus injection. Singal et al and Uchida et al both report a case of delayed emergence in a patient with severe hepatic impairment 28,102 . Shimamoto et al 126 showed that patients with delayed emergence, had a higher BMI, were older, and had a lower plasma albumin concentration.…”
Section: Discussionmentioning
confidence: 99%